Silvicultural value chain analysis of short rotation Eucalyptus grandis x urophylla stands in coastal Zululand - Graham, Daniel John (Stellenbosch : Stellenbosch University, 2018)
Thesis (MScFor)--Stellenbosch University, 2018.